2011
DOI: 10.1007/s00213-011-2236-1
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life experiences, alcohol consumption, and alcohol use disorders: the epidemiologic evidence for four main types of stressors

Abstract: Background Exposure to stress is potentially important in the pathway to alcohol use and alcohol use disorders. Stressors occur at multiple time points across the life course, with varying degrees of chronicity and severity. Method We review evidence from epidemiologic studies on the relationship between four different stressors (fateful/catastrophic events, child maltreatment, common adult stressful life events in interpersonal, occupational, financial, and legal domains, and minority stress) and alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
310
5
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(336 citation statements)
references
References 191 publications
(245 reference statements)
16
310
5
5
Order By: Relevance
“…Research shows that one of the ways police officers cope with stress is by engaging in alcohol consumption (Brady & Pharm, 1999;Keyes, Hatzenbuehler, & Hasin, 2011;Siegrist & Rodel, (2006) also suggested the likely habitual use of tobacco by police officers. According to Smith, Devine, Leggat, & Ishitake, (2005).…”
Section: Coping Strategy: Alcohol and Tobacco Usementioning
confidence: 99%
“…Research shows that one of the ways police officers cope with stress is by engaging in alcohol consumption (Brady & Pharm, 1999;Keyes, Hatzenbuehler, & Hasin, 2011;Siegrist & Rodel, (2006) also suggested the likely habitual use of tobacco by police officers. According to Smith, Devine, Leggat, & Ishitake, (2005).…”
Section: Coping Strategy: Alcohol and Tobacco Usementioning
confidence: 99%
“…17 For example, women have nearly twice the prevalence of mental health disorders, including major depression, generalized anxiety, panic disorder, social phobia, and specific phobia, compared with men; in contrast, men show higher prevalences of alcohol and drug dependence. 18,19 Researchers have previously described a ''liability model'' of gender differences related to internalizing versus externalizing problems, 20 such that women tend to have a greater prevalence of internalizing disorders, while men have a higher prevalence of externalizing disorders. 17,18 Accordingly, the patterns of the associations between discrimination, mental health, and substance use disorders may differ by gender, such that sexual minority women who experience discrimination are more vulnerable to mental health disorders and sexual minority men who experience discrimination are more vulnerable to substance use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is inconsistent evidence regarding whether risk for adverse alcohol-related outcomes associated with SLEs varies with gender (Keyes et al, 2011). A number of studies have found a stronger association of childhood maltreatment with excessive drinking and alcohol use disorders in women than men (Enoch, 2011;Simpson and Miller, 2002).…”
mentioning
confidence: 99%